Recurrent nocturnal hypoglycemic hemiplegia: a case report and review of the literature - Hanako Toyama; Kazuyuki Takahashi; Tatsunori Shimizu; Izumi Otaka; Sakiko Abe; Shunsuke Kato; Sayaka Ando; Takehiro Sato; Tsukasa Morii; Hiroki Fujita; Hironori Waki (Endocrine Journal)
A 67-year-old man with type 1 diabetes, Cronkhite-Canada syndrome, and membranous nephropathy who received insulin therapy was admitted to our hospital with right hemiplegia and dysarthria. Brain magnetic resonance imaging revealed a lesion with a high diffusion-weighted imaging signal and low apparent diffusion coefficient signal in the posterior limb of the left internal capsule. He was hypoglycemic with a blood glucose level of 56 mg/dL (3.1 mmol/L). Following glucose administration, the patient’s symptoms resolved within several hours. The patient experienced similar transient hypoglycemic hemiplegia at midnight, three times within 10 days. In a literature review of 170 cases of hypoglycemic hemiplegia, 26 cases of recurrent hemiplegia were investigated. Recurrent hypoglycemic hemiplegia occurs more frequently on the right side than on the left side, and most recurrences occur within approximately a week, almost exclusively at midnight and in the early morning. We speculate that hypoglycemia-associated autonomic failure may be involved in the nocturnal recurrence of episodes. In our patient, depleted endogenous insulin secretion and lipodystrophy at the injection site, may have acted as additional factors, leading to severe hypoglycemia despite the absence of apparent autonomic neuropathy. Clinically, it is important to recognize hypoglycemia as a cause of hemiplegia to avoid unnecessary intervention and to maintain an appropriate blood glucose level at midnight and early in the morning to prevent recurrent hypoglycemic hemiplegia.